Dialektika Gaya Bahasa al-QurâÃ¢n dan Budaya Arab Pra-Islam: Sebuah Kajian Sosiologi Bahasa - Muzakki, Akhmad (ISLAMICA: Jurnal Studi Keislaman, 2007)
The linguistic style of the Qurâan is closely associated with the psychological state of the Arabs as well as with their overall civilization. When speaking of the truthâespecially the truth that has to do with the unseenâIslam puts into consideration this psychological aspect and conveys this kind of truth in a metaphorical or symbolical language. By this, it is meant that the language of the Qurâan is a product of the dialectical process between what the Qurâan ought to say and the contextual reality. Therefore, the Qurâan must be understood in relation to the contextual reality so as to show its ardent adaptability to a given reality. The linguistic studies have thus far shown that when certain texts are read in isolation from the social constructs in which they are written as well as from their author, the texts will loose their true meaning and their communicative function. A literary work is above all a response to a social condition that takes place in a giventime and space.